2017
DOI: 10.1302/0301-620x.99b5.bjj-2016-0745.r1
|View full text |Cite
|
Sign up to set email alerts
|

Early migration of a partially cemented fluted glenoid component inserted using a cannulated preparation system

Abstract: Rapid early migration associated with focal lucency and absence of osseointegration was observed in three of 11 glenoid components, suggesting that lack of initial stability leads to early movement and failure of osseointegration. Cite this article: 2017;99-B:674-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…A total of 25 studies were noncomparative. Of these studies, 9 examined keeled glenoid fixations9, 12, 15, 19, 23, 31, 50, 51, 54 and 16 examined pegged glenoid fixations5, 7, 14, 25, 26, 27, 28, 29, 35, 36, 38, 39, 42, 45, 49, 53 (Table I). Among these studies, 10 reported ASES scores, 16 reported Constant scores, 19 reported radiolucency rates, and 19 reported revision rates.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 25 studies were noncomparative. Of these studies, 9 examined keeled glenoid fixations9, 12, 15, 19, 23, 31, 50, 51, 54 and 16 examined pegged glenoid fixations5, 7, 14, 25, 26, 27, 28, 29, 35, 36, 38, 39, 42, 45, 49, 53 (Table I). Among these studies, 10 reported ASES scores, 16 reported Constant scores, 19 reported radiolucency rates, and 19 reported revision rates.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 13 articles were eligible for inclusion in the qualitative analysis. [18][19][20][21][22][23][24][25][26][27][28][29][30] The corresponding PRISMA chart of the literature search results is shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…One study 25 was Level II, while 12 studies [18][19][20][21][22][23][24][26][27][28][29][30] were Level IV.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations